Refrigerated platelets stored in whole blood up to 5 days adhere to thrombi formed during hemorrhagic hypotension in rats. (18th December 2016) - Torres Filho, I. P.; Torres, L. N.; Valdez, C.; Salgado, C.; Cap, A. P.; Dubick, M. A.
Abstract : Essentials In vivo function of platelets stored at various conditions was studied in normo‐ and hypotension. Refrigerated platelets stored up to 5 days performed as well as those stored at room temperature. Platelet adhesion and thrombus formation were higher in ruptured vessels of hemorrhaged animals. In vivo data suggest that refrigerated platelets are hemostatically effective during hypotension. Summary: Background: There is renewed interest in the therapeutic use of cold‐stored platelets for bleeding patients. However, critical information is absent or partially available in vitro . Therefore, thrombus formation and platelet adhesion were studied in vivo, in situ, using bleeding and thrombosis models in instrumented rats, and confocal intravital videomicroscopy. Objectives We tested the hypothesis that refrigerated (4 °C) platelets (stored for 24 h or 5 days) participated in thrombus formation as well as platelets stored at room temperature (RT, 22 °C). This hypothesis was tested in normovolemia and hemorrhagic hypotension. Methods & Results: After fluorescently‐labeled platelet infusion, endothelial injury and vessel rupture were laser‐induced in cremaster microvessels and platelet adhesion in > 230 developing thrombi was evaluated. Blood samples were collected for biochemistry and coagulation assays while multiple systemic physiologic parameters were recorded. Hemorrhagic hypotension study animals were subjected to 40% hemorrhage, leading to hypotension and hemodilution, during in vivo platelet adhesion assessments. The fluorescence intensity associated with labeled platelet adherence provided a quantitative index of adhesion. Cold‐stored platelets performed as well as those stored at RT in normovolemic animals. During hypotension, cold‐stored platelets still performed as well as RT‐stored platelets, whereas platelet adhesion and thrombus formation were increased relative to normovolemic animals, in bleeding model experiments. Conclusions: We found the methodology suitable for evaluating platelet function in vivo after different storage conditions in fully monitored animals. Refrigerated platelets (stored up to 5 days) participated as well as RT‐stored platelets in thrombi formed after hemorrhage, suggesting that refrigerated platelets are effective during hypotensive situations.